Study of the dependence of relative elongation on mechanical stress of polyvinyl chloride films - Kupchishin, А.И.; Niyazov, М.Н. (Recent Contributions to Physics, 2024)
The dependence of relative elongation on mechanical stress in polyvinyl chloride samples of various widths and working lengths was experimentally studied. The purpose of the study was to study the dependence of deformation on mechanical stress of polyvinyl chloride films of various sizes (width and length). The scientific and practical significance of the work lies in the fact that the data can serve as the basis for future research. Polyvinyl chloride film with a thickness of 100 microns was chosen as the material under study. The film sheets were cut into strips 3, 5, 7, 10 mm wide using a special cutting device with adjustable sample cutting width and length. The working length of the samples was: 4, 5, 6, 7, 8 cm. The tests were carried out on a special tensile testing machine RU-50. This setup is designed to study the dependence of strain (relative elongation) ε on stress σ. Significant changes in the mechanical properties of the material were discovered depending on various geometric parameters. The data obtained are satisfactorily described by the authors' models. The value of this study lies in the fact that the results of the work, according to the authors, will serve as an incentive to improve the mechanical properties of the research object.